1987
DOI: 10.1128/mcb.7.7.2506
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and characterization of the cys-3 regulatory gene of Neurospora crassa.

Abstract: The regulatory gene cys-3+ controls the synthesis of a number of enzymes involved in sulfur metabolism. cys-3 mutants show a multiple loss of enzymes in different pathways of sulfur metabolism. The cys-3+ gene was isolated by transformation of an aro-9 qa-2 cys-3 inl strain with a clone bank followed by screening with the "sib selection" method. The library used (pRALl) contained inserts of Sau3a partial digest fragments of about 9 kilobases as well as the Neurospora qa-2+ gene. Double selection for qa-2+ and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 25 publications
1
41
0
Order By: Relevance
“…The Met4 protein is a Leu-zipper-containing transcriptional activator of the bZIP type (Thomas et al, 1992;Kuras and Thomas, 1995). In Neurospora crassa the Cys3 protein, which is also a bZIP-type DNA-binding protein, serves as a positive activator of sulfur-regulated genes (Marzluf, 1968;Paietta et al, 1987;Paietta, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…The Met4 protein is a Leu-zipper-containing transcriptional activator of the bZIP type (Thomas et al, 1992;Kuras and Thomas, 1995). In Neurospora crassa the Cys3 protein, which is also a bZIP-type DNA-binding protein, serves as a positive activator of sulfur-regulated genes (Marzluf, 1968;Paietta et al, 1987;Paietta, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…The main component of the sulfur regulatory circuit is a positively acting bZIP transcription factor, which in yeast is a heterodimer consisting of two proteins, Met28p and Met4p (442)(443)(444). In filamentous fungi, like N. crassa and A. nidulans, one homodimeric bZIP activator (N. crassa CYS-3, A. nidulans MetR) is responsible for sulfur network regulation (445,446). However, recent studies revealed that A. nidulans and other members of the Eurotiales may possess exchangeable homo-/heterodimeric regulatory networks comprised of MetR and paralogous bZIP transcription factor MetZ (447).…”
Section: T Reesei T Atroviride and T Virens Have A Single Orf Enmentioning
confidence: 99%
“…One recent study to examine the operation of the sulfur control circuit involved the cloning and subsequent analysis of the expression of the cys-3+ control gene (21). To understand the sulfur regulatory circuit, it is obviously very * Corresponding author.…”
mentioning
confidence: 99%